Carbazole Containing Copolymers: Synthesis, Characterization, and Applications in Reversible Holographic Recording - Bénédicte Mailhot-Jensen; Stefan Robu; Agnès Rivaton; Jean-François Pilichowski; Arcadi Chirita; Ekaterina Chilat; Galina Dragalina (International Journal of Photoenergy)
Carbazolic copolymers have been developed to be used in reversible holographic recording. This paper describes a complete analysis, from synthesis of the material to its applications, together with the corresponding characterizations. The investigated materials were photosensitive copolymers obtained from carbazolylalkylmethacrylates (CEM) and octylmethacrylate (OMA). A detailed investigation was undertaken involving infrared spectroscopy and NMR techniques, 1H, 13C, COSY, and HSQC, in order to establish the chemical structure and the composition of the copolymers. Holographic recording characteristics were investigated with one- and two-layer photothermoplastic carriers. The two-layer carrier contains separate photosensitive and thermoplastic layers and gives the best holographic response. The surface of microstructured samples has been characterized by atomic force microscopy analysis. It is shown that via a photothermoplastic recording process, it is possible to record and read holograms practically in real time (~3 s) with a diffraction efficiency of 10% and a spatial resolution higher than 1000 mm−1.